Rare Presentation of Liver Abscess - Arifin, BA; Rauf, M; Salleh, MS; Nyin, LY (IIUM Medical Journal Malaysia, 2019)
Liver abscess can present in various manners and in some cases causes delays and misdiagnoses. We are reporting 2 cases of rare presentation of liver abscess. The first case is a 64-year-old gentleman presented with right hypochondriac pain since August 2017 and diagnosed to have liver abscess. He was treated with antibiotics and serial imaging for reassessment. However, he presented again this year with right sided anterior abdominal wall swelling. Abdominal computed tomography (CT) showed anterior abdominal wall collection with extension into right internal and external oblique muscles with communication with liver collection at segment VII. An open incision and drainage was performed with drain inserted over the anterior abdominal wall collection. He was then referred to hepatobiliary center for further management. Second case is a 30-year-old gentleman underlying Beta thalassemia major- post splenectomy with Klebsiella pneumonia bacteremia noted to have left multiseptated collection with posterobasal consolidation and left parapneumonic effusion which was initially misdiagnosed as splenic abscess. However, with further imaging was confirmed to be a left liver abscess with focal discontinuity in left hemidiaphragm, which communicates between liver abscess and enlarging left lower loculated pleural effusion. Radiological guided pigtail catheter was inserted and serial imaging showed collection decreasing in size. Extra-abdominal manifestation of a liver abscess is a rare clinical entity and is not well documented. The advent of ultrasound and CT scan, there has been improvement in the rate of early diagnosis even with these uncommon presentations. Percutaneous drainage with antimicrobial therapy remains gold standard for a non-ruptured abscess. Surgical intervention should be considered for large, complex, multiseptated abscesses or in whom percutaneous drainage has failed.